Polymeric immunoglobulin receptor promotes tumor growth in hepatocellular carcinoma. Issue 6 (28th April 2017) - Yue, Xihua; Ai, Jing; Xu, Yang; Chen, Yi; Huang, Min; Yang, Xinying; Hu, Bo; Zhang, Haotian; He, Changxi; Yang, Xinrong; Tang, Weiguo; Peng, Xia; et al.
Abstract : Deregulation of the immune system is believed to contribute to cancer malignancy, which has led to recent therapeutic breakthroughs facilitating antitumor immunity. In a malignant setting, immunoglobulin receptors, which are fundamental components of the human immune system, fulfill paradoxical roles in cancer pathogenesis. This study describes a previously unrecognized pro‐oncogenic function of polymeric immunoglobulin receptor (pIgR) in the promotion of cell transformation and proliferation. Mechanistically, pIgR overexpression is associated with YES proto‐oncogene 1, Src family tyrosine kinase (Yes) activation, which is required for pIgR‐induced oncogenic growth. Specifically, pIgR activates the Yes‐DNAX‐activating protein of 12 kDa‐spleen tyrosine kinase‐Rac1/CDC42‐MEK (extracellular signal‐regulated kinase kinase)/ERK (extracellular signal‐regulated kinase) cascade in an immunoreceptor tyrosine‐based activating motif (ITAM)‐dependent manner to promote cell transformation and tumor growth, although pIgR itself does not contain an ITAM sequence. Additionally, the combination of pIgR and phosphorylated Yes (p‐Yes) levels serves as a prognostic biomarker for hepatitis B surface antigen–positive and early‐stage hepatocellular carcinoma (HCC) patients. Moreover, pharmacological targeting of MEK/ERK or Yes represents a therapeutic option for the subgroup of patients with pIgR/p‐Yes–positive HCC based on our results with both cancer cell‐line–based xenografts and primary patient‐derived xenografts. Conclusion : Our findings reveal the molecular mechanism by which pIgR promotes cancer malignancy, suggest the clinical potential of targeting this pathway in HCC, and provide new insight into the oncogenic role of immunoglobulin receptors. (Hepatology 2017;65:1948‐1962).